Late Pulmonary Embolism In Long Covid Syndrome Patient: A Fatal Case Report - Eko Budiono; Ika Trisnawati; Subroto Subroto (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Long COVID syndrome refers to a condition in which individuals experience a range of persistent symptoms and health issues following the acute phase of a COVID-19 infection. A 26-years-old Indonesian lady presented to ER department with complaining shortness of breath since 10 days before admission. Patient had history of Covid-19 one year ago, since then she always complaining shortness of breath. Research Objectives to identify the range of symptoms that persist in individuals with long COVID, characterize the severity and variability of these persistent symptoms among affected individuals, to Evaluate the Duration and Severity of Long COVID Symptoms. General condition unwell, BP 143/89 mmhg HR 116 x/mnt RR 24 x/mnt T 36.4°C BMI 19.1 kg/m2. SpO2 77% in room air, then 94% with NRM 15 lpm. On physical examinations showed thorax vesicular +/+, ronchi -/-, wheezing -/-. Lung auscultation was normal and abdominal palpation was unremarkable. Laboratory test revealed CBC, LFT, RFT,  Electrolyte normal,  Lac 2.0  D-dimer 1183 Fibrinogen 276 LDH 181, ECG showed RAD RVH global T inverted, S1 (+) Q3 (-), T3 (+), CXR Pneumonia bilateral typical covid. Assessment Long covid syndrome with respiratory failure type 1, severe ARDS. Treatment Antibiotics, nebulizer farbivent: fluticasone/ 8 hrs, Spiriva 1x2 puff, heparinizations, Unfortunately the patient passed away on 23 May 2023. This case report describes an unusual case in which an established pulmonary embolism (PE) was detected more than 1 year in a patient declared cured of SARS-CoV2 infection. Conclusion This case showed that the risk of late pulmonary embolism remains high in Long Covid Syndrome patient. Early diagnosis and treatment should be addressed quickly to prevent the mortality